2016
DOI: 10.1080/19371918.2016.1160346
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Interventions to Reduce Alcohol Use Among Patients with Hepatitis C: A Systematic Review

Abstract: Alcohol use is a barrier to pharmacologic treatment for hepatitis C virus (HCV). It is advantageous for medical and clinical social workers engaged in HCV care to be knowledgeable of behavioral interventions that can be used to reduce alcohol use among patients with HCV. This article identifies and describes studies that designed and implemented behavioral interventions to reduce alcohol use among patients with HCV in clinical settings. To achieve this goal, this article conducts a rigorous systematic review t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Due to the harm alcohol confers on patients with liver conditions, and the fact that treatment of many liver conditions requires repeated visits, both experts and national organizations, including the American Association for the Study of Liver Disease, have called for the provision of alcohol screening, brief intervention, and behavioral and/or medication treatment as needed for patients with chronic liver disease who drink at unhealthy levels [ 14 , 15 ]. Prior studies have suggested that evidence-based interventions recommended in primary care and other health settings are appropriate for patients being treated in liver-specific care settings [ 1 , 16 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the harm alcohol confers on patients with liver conditions, and the fact that treatment of many liver conditions requires repeated visits, both experts and national organizations, including the American Association for the Study of Liver Disease, have called for the provision of alcohol screening, brief intervention, and behavioral and/or medication treatment as needed for patients with chronic liver disease who drink at unhealthy levels [ 14 , 15 ]. Prior studies have suggested that evidence-based interventions recommended in primary care and other health settings are appropriate for patients being treated in liver-specific care settings [ 1 , 16 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the biological sequelae of alcohol use on the liver and HCV treatment ineligibility associated with alcohol are well established (McCartney & Beard, 2010; Sims et al, 2017; Sims, Maynard, & Melton, 2016; Singal & Anand, 2007; Stroffolini et al, 2017; Vieira-Castro & Oliveira, n.d. ; Younossi et al, 2013), available data on the consequences of active alcohol use on quality of life, functioning, and coping in HCV patients are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates indicate that 57%-67% of people with hepatitis C virus (HCV) smoke cigarettes (Basseri et al, 2010; Chew et al, 2015; Shuter et al, 2016; Zimmermann et al, 2016), 65%-73% consume alcohol (Drumright et al, 2011; North et al, 2014; Taylor, Denniston, Klevens, McKnight-Eily, & Jiles, 2016; Tsai, Ford, Li, & Zhao, 2012), and 57%-65% use illicit drugs (Sims et al, 2016; Whitehead, Hearn, Trenz, Burrell, & Latimer, 2014). Alcohol use and smoking independently accelerate progression to HCV-related liver disease and cancer (Jeng et al, 2009; Lok et al, 2009; Soeda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use and smoking independently accelerate progression to HCV-related liver disease and cancer (Jeng et al, 2009; Lok et al, 2009; Soeda et al, 2012). Ethanol destroys cells that carry out primary liver functions and amplifies liver cancer risk 100-fold in patients with HCV (Osna, Ganesan, & Kharbanda, 2015; Sims, Maynard, & Melton, 2016; Younossi, Zheng, Stepanova, Venkatesan, & Mir, 2013). Cigarette smoke contains several cytotoxic chemicals metabolized in the liver that cause chronic inflammation leading to cell death and contribute to viability and replication of HCV (Costiniuk et al, 2016; Zhao, Li, & Taylor, 2013).…”
Section: Introductionmentioning
confidence: 99%